Service organization protocol for coping with undergraduate students' psychological distress: a collective construction - Tatiane Carolina Martins Machado Rodrigues; Guilherme Correa Barbosa; Vera Lúcia Pamplona Tonete (Associação Brasileira de Enfermagem, 2023)
ABSTRACT Objective: to report on the experience of the elaboration process of a service organization protocol for coping with public undergraduate students' psychological distress in the countryside of São Paulo. Method: experience report on protocol production, an action research product, carried out according to the health care and service organization protocol model, made possible by remote meetings with 33 professionals linked to the management and services of the university's health and social assistance departments. Results: collective protocol production provided an opportunity for an institutional agreement on educational, therapeutic and support actions, to be developed in groups or individually with students, with provision for permanent education with civil servants. Final considerations: this experience made it possible to list specific actions to face undergraduate students' psychological distress, bringing health professionals closer to those in management, promoting the exchange of concepts and practices to re-signify and transform the work developed.